Strategy of Integrated Salaf Curriculum in Madrasah Aliyah to Improve the Graduates’ Quality - Fadillah, Haris; Trisnamansyah, Sutaryat; Insan, Husen Saeful; Sauri, Supyan (Journal of Education Reseach and Evaluation, 2021)
Islamic boarding schools must follow the national curriculum to compete in real life. Therefore, many Islamic boarding schools have changed their education system Islamic boarding schools still adhere to the Salaf (traditional) system. However, they are gradually adopting a national education system in which the national curriculum is integrated into it. This study aims to analyze the Salaf curriculum management plan, curriculum preparation, curriculum implementation, and evaluation of curriculum management. This research uses descriptive qualitative with case studies in Islamic boarding schools. The method used to collect data is interviews, observation, documentation, instruments. The instrument used to collect information is a questionnaire. The technique used to analyze the data is descriptive qualitative analysis. Research results Identify that the management of the Salaf curriculum, which is integrated with the Madrasah Aliyah curriculum that is appropriately designed, can improve the quality of graduates. Salaf curriculum management administration combined with Madrasah Aliyah by paying attention to school subjects can improve the quality of graduates. The management of the Salaf curriculum integrated with the Madrasah Aliyah curriculum can be done through extracurricular and extracurricular activities. The control of the Salaf curriculum, which is integrated with the Madrasah Alliyah curriculum, which is collective and formative, will affect the quality of graduates. Implementing the salaf curriculum combined with the Madrasah Aliyah curriculum to improve the quality of graduates does not require additional subjects. And the issues used to strengthen the Salaf curriculum, which is integrated with the Madrasah Aliyah curriculum, are the yellow book, tahfidzul Qur'an, and empowering school resources.